Factors Related to Soil Transmitted Helminth Infection on Primary School Children (Unnes Journal of Public Health, 2018)
ABSTRACT Infeksi Soil Transmitted Helminth (STH) is the third ranks of the top 10 common infectious diseases in the world with an incidence rate of about 1.4 billion per year. The incidence of STH in Indonesia is still quite high. This figure occurs in primary school students of 60-80%, while for all ages of 40% -60%. The purpose of this study was to determine factors related to STH infection in elementary school children at primary school of Moyudan Sleman. The type of research used was analytic observational with the cross-sectional design. The population in this study were all students of class I, II, and III in Moyudan Sleman primary school with total sampling technique of 60 respondents. Data analysis used chi-square. The test results showed that the habit of hand washing before eating (sig= 0.010; RP= 3.850), the habit of hand washing after defecating(sig= 0.007; RP= 4.571), nail hygiene (sig= 0.179; RP= 2.138), the habit of wearing footwear (sig= 0.008; RP= 3.714), and bowel habits (sig= 0.004; RP= 4.000). It can be concluded that there was a relationship between hand washing before eating, hand washing after defecating, the habit of wearing footwear, bowel habits and STH infection on the students of Moyudan Sleman primary school but there was no relationship between nail hygiene and STH infection. ABSTRAK Infeksi Soil Transmitted Helminth (STH) adalah penyakit yang menempati urutan ketiga dari 10 penyakit menular di dunia dengan tingkat kejadian sekitar 1,4 miliar per tahun. Insiden STH di Indonesia masih cukup tinggi. Angka tersebut terjadi pada siswa di sekolah dasar mencapai 60-80%, sedangkan untuk semua usia berkisar antara 40%-60%. Tujuan dari penelitian ini adalah untuk mengetahui faktor yang berhubungan dengan infeksi STH pada anak sekolah dasar di SD Negeri Moyudan Sleman. Penelitian ini adalah observasional analitik dengan rancangan cross sectional. Populasi dalam penelitian ini adalah semua siswa kelas I, II, dan III di SD Moyudan Sleman dengan teknik total sampling yaitu 60 responden. Analisis data menggunakan uji chi-squre. Hasil uji menunjukkan bahwa mencuci tangan sebelum makan (sig= 0,010; RP= 3,850), mencuci tangan setelah buang air besar (sig= 0,007; RP= 4,571), kebersihan kuku (sig= 0,179; RP= 2,138), kebiasaan memakai alas kaki (sig= 0,008; RP= 3,714), dan perilaku buang air besar (sig= 0,004; RP= 4,000). Disimpulkan bahwa ada hubungan antara mencuci tangan sebelum makan, mencuci tangan setelah BAB, kebiasaan memakai alas kaki, dan perilaku buang air besar dengan infeksi STH pada anak-anak sekolah dasar Moyudan Sleman, sementara kebersihan kuku tidak memiliki hubungan dengan infeksi STH. Kata kunci: Infeksi STH, faktor risiko, sekolah dasar ABSTRACT Infeksi Soil Transmitted Helminth (STH) is the third ranks of the top 10 common infectious diseases in the world with an incidence rate of about 1.4 billion per year. The incidence of STH in Indonesia is still quite high. This figure occurs in primary school students of 60-80%, while for all ages of 40% -60%. The purpose of this study was to determine factors related to STH infection in elementary school children at primary school of Moyudan Sleman. The type of research used was analytic observational with the cross-sectional design. The population in this study were all students of class I, II, and III in Moyudan Sleman primary school with total sampling technique of 60 respondents. Data analysis used chi-square. The test results showed that the habit of hand washing before eating (sig= 0.010; RP= 3.850), the habit of hand washing after defecating(sig= 0.007; RP= 4.571), nail hygiene (sig= 0.179; RP= 2.138), the habit of wearing footwear (sig= 0.008; RP= 3.714), and bowel habits (sig= 0.004; RP= 4.000). It can be concluded that there was a relationship between hand washing before eating, hand washing after defecating, the habit of wearing footwear, bowel habits and STH infection on the students of Moyudan Sleman primary school but there was no relationship between nail hygiene and STH infection.